Halfway to the grave eaudiobook A night huntress novel. - Frost, Jeaniene (Night Huntress, 2010)
Half-vampire Catherine Crawfield is going after the undead with a vengeance, hoping that one of these deadbeats is her father—the one responsible for ruining her mother's life. Then she's captured by Bones, a vampire bounty hunter, and is forced into an unlikely partnership. In exchange for help finding her father, Cat agrees to train with the sexy night stalker until her battle reflexes are as sharp as his fangs. She's amazed she doesn't end up as his dinner ... are there actually good vampires? Pretty soon, Bones will have her convinced that being half-dead doesn't have to be all bad. But before she can enjoy her status as kick-ass demon hunter, Cat and Bones are pursued by a group of killers. Now Cat will have to choose a side—and Bones is turning out to be as tempting as any man with a heartbeat.